Extraction of Cellulose Nanofibrils (CNFs) from Pomelo Peel via Hydrothermal Auxiliary Alkali Treatment Combined with Ball-Milling (Journal of Fiber Bioengineering and Informatics, 2023)
The pomelo peel, a by-product of pomelo processing, is predominantly discarded. To fully exploitthe pomelo peel resources and contribute to environmental improvement and resource recycling, thisstudy reports a green method for extracting cellulose nanofibrils (CNFs) from pomelo peel throughhydrothermal-assisted alkali treatment. Lemon juice is employed for further ball milling treatment topurify the CNFs. The chemical structure, crystallinity, thermal stability, and microstructure of pomelopeel powder and CNFs are analyzed. The study results demonstrate that the combination of alkalitreatment, hydrothermal processing, bleaching, and ball milling progressively eliminates hemicellulose,lignin, and other impurities from the pomelo peel, yielding high-quality CNFs. The CNFs retain thenatural cellulose structure, with enhanced thermal stability and crystallinity. The diameters of the CNFsrange from 2-30 nm. This method employs lower NaOH concentrations than previous studies, resultingin CNFs with higher crystallinity and smaller diameters. This study provides a promising method forenhancing the value-added of pomelo peel and increasing the volume of CNF production.
Keywords: Pomelo peel; Cellulose nanofibers; Hydrothermal; Extraction